2015
DOI: 10.1136/jclinpath-2015-203207
|View full text |Cite
|
Sign up to set email alerts
|

Gene of the month:KIT

Abstract: Deranged pathway activation and KIT mutations occur in numerous solid and haematological malignancies, with gain-of-function mutations being the most common demonstrable abnormality. Through a complex series of interactions, activation of the KIT receptor tyrosine kinase leads to cell survival, evasion of apoptosis, angiogenesis, dysregulated cell cycle control and promotion of tumourigenesis. The KIT receptor tyrosine kinase is a well-studied therapeutic target in human malignancies. The KIT mutational status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…CD117 has been found to be present in a large assortment of tumours, including carcinomas, sarcomas, and haematopoietic malignancies. 8 However, when combined with morphology and other ancillary studies, it can be used in a panel to help differentiate a variety of entities. In fact, previous studies have shown that~30% of all myelomas are positive for CD117.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD117 has been found to be present in a large assortment of tumours, including carcinomas, sarcomas, and haematopoietic malignancies. 8 However, when combined with morphology and other ancillary studies, it can be used in a panel to help differentiate a variety of entities. In fact, previous studies have shown that~30% of all myelomas are positive for CD117.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] CD117, a type III tyrosine kinase receptor, is encoded by the KIT proto-oncogene, and shows aberrant expression in myelomatous plasma cells. 8,9 In fact, in one study of 13 cutaneous plasmacytomas, all 13 expressed CD117, including five that had plasmablastic morphology. 10 On the other hand, very few PBLs have been reported to express this protein.…”
Section: Introductionmentioning
confidence: 99%
“…Mutated KIT homodimerizes in a ligand-independent way. Activated KIT initiates RAS/MAPK, PI3K/AKT/mTOR and JAK/STAT3 signaling [ 49 – 51 ] (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sporadically, melanoma, non-GIST stromal tumors and breast cancer have been signaled. KIT mutations could be implied in the arousal of the former [ 49 ]; the latter two are likely incidental. Sometimes, non-GIST signs are the first reason for patients to seek medical help [ 15 , 32 , 35 , 41 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In mouse strains with KIT mutations several defects are observed such as anemia, infertility, susceptibility to infection, and pigment loss. Spontaneous mutations in KIT resulting in constitutive activation occur in human tumors including gastrointestinal stromal tumors (GIST), acute myelogenous leukemia (AML), melanoma, and systemic mastocytosis (4). Small molecule inhibitors that target KIT have had significant clinical success, most notably in the treatment of GIST where imatinib is now the standard of care for patients with high risk disease (5).…”
Section: Introductionmentioning
confidence: 99%